Cobalt and precious metals in sulphides of peridotite xenoliths and inferences concerning their distribution according to geodynamic environment: A case study from the Scottish lithospheric mantle - Hughes, HS; McDonald, I; Faithfull, JW; Upton, BG; Loocke, M (Lithos, 2015)
This is the final version of the article. Available from Elsevier via the DOI in this record. Abundances of precious metals and cobalt in the lithospheric mantle are typically obtained by bulk geochemical analyses of mantle xenoliths. These elements are strongly chalcophile and the mineralogy, texture and trace element composition of sulphide phases in such samples must be considered. In this study we assess the mineralogy, textures and trace element compositions of sulphides in spinel lherzolites from four Scottish lithospheric terranes, which provide an ideal testing ground to examine the variability of sulphides and their precious metal endowments according to terrane age and geodynamic environment. Specifically we test differences in sulphide composition from Archaean-Palaeoproterozoic cratonic sub-continental lithospheric mantle (SCLM) in northern terranes vs. Palaeozoic lithospheric mantle in southern terranes, as divided by the Great Glen Fault (GGF). Cobalt is consistently elevated in sulphides from Palaeozoic terranes (south of the GGF) with Co concentrations > 2.9 wt.% and Co/Ni ratios > 0.048 (chondrite). In contrast, sulphides from Archaean cratonic terranes (north of the GGF) have low abundances of Co (< 3600 ppm) and low Co/Ni ratios (< 0.030). The causes for Co enrichment remain unclear, but we highlight that globally significant Co mineralisation is associated with ophiolites (e.g., Bou Azzer, Morocco and Outokumpu, Finland) or in oceanic peridotite-floored settings at slow-spreading ridges. Thus we suggest an oceanic affinity for the Co enrichment in the southern terranes of Scotland, likely directly related to the subduction of Co-enriched oceanic crust during the Caledonian Orogeny. Further, we identify a distinction between Pt/Pd ratio across the GGF, such that sulphides in the cratonic SCLM have Pt/Pd ≥ chondrite whilst Palaeozoic sulphides have Pt/Pd < chondrite. We observe that Pt-rich sulphides with discrete Pt-minerals (e.g., PtS) are associated with carbonate and ...